Perancangan Sistem Informasi Administrasi Murid Berbasis Web Studi Kasus PAUDQu AR-RAFI' - Moch. Dira Issyari; Anisa Tasyah; Dwi Fadillah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PAUDQU AR-RAFI' is a place for children's education located in . So far, the system running for administrative activities at PAUDQU AR-RAFI' has not used a computerized system. During this pandemic, teaching and learning activities are carried out online, making the management of school administrative activities increasingly limited and hampered. Several things that underlie the problems in this research lie in the process of managing students, teachers, student grades, student payment transactions and problems. The design and development of this system aims to facilitate teachers and students in processing and obtaining information about PAUDQU AR-RAFI administration activities. In its development, the method used is the Software Development Life Cycle (SDLC) method with the Prototype model.